2021
DOI: 10.1002/cmdc.202100618
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Dithiobisacetamides as Novel Urease Inhibitors

Abstract: Thirty-eight disulfides containing N-arylacetamide were designed and synthesized in an effort to develop novel urease inhibitors. Biological evaluation revealed that some of the synthetic compounds exhibited strong inhibitory potency against both cell-free urease and urease in intact cell with low cytotoxicity to mammalian cells even at concentration up to 250 μM. Of note, 2,2'-dithiobis(N-(2-fluorophenyl)acetamide) (d7), 2,2'-dithiobis(N-(3,5-difluorophenyl)acetamide) (d24), and 2,2'-dithiobis(N-(3-fluorophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the N-(2-pyridyl)acetamide series (compounds 5j-l), the 5-substituted compounds 5j and 5l respectively with methyl and chloro substituents showed approximately the same inhibitory activity against urease while 6-methyl derivative 5k shows less inhibitory activity compared to compounds 5j and 5l. The comparison of anti-urease activities of the new cysteine-N-arylacetamide derivatives 5a-l with cysteine derivatives A-B and N-arylacetamide derivatives C-D demonstrated that our new compounds inhibit the target enzyme urease much more potently than the template compounds A-D [17,23,24]. For example, as can be seen in Scheme 2, the comparison of IC 50 values of the new cysteine-N-arylacetamide derivatives 5 with their corresponding analogs of 2-((5-amino-1,3,4-thiadiazol-2-yl)thio)-N-arylacetamide derivatives D revealed that replacement of 2-((5-amino-1,3,4-thiadiazol-2-yl)thio) moiety of these compounds with cysteine unit improved anti-urease activity [24].…”
Section: In Vitro Urease Inhibitory Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…In the N-(2-pyridyl)acetamide series (compounds 5j-l), the 5-substituted compounds 5j and 5l respectively with methyl and chloro substituents showed approximately the same inhibitory activity against urease while 6-methyl derivative 5k shows less inhibitory activity compared to compounds 5j and 5l. The comparison of anti-urease activities of the new cysteine-N-arylacetamide derivatives 5a-l with cysteine derivatives A-B and N-arylacetamide derivatives C-D demonstrated that our new compounds inhibit the target enzyme urease much more potently than the template compounds A-D [17,23,24]. For example, as can be seen in Scheme 2, the comparison of IC 50 values of the new cysteine-N-arylacetamide derivatives 5 with their corresponding analogs of 2-((5-amino-1,3,4-thiadiazol-2-yl)thio)-N-arylacetamide derivatives D revealed that replacement of 2-((5-amino-1,3,4-thiadiazol-2-yl)thio) moiety of these compounds with cysteine unit improved anti-urease activity [24].…”
Section: In Vitro Urease Inhibitory Activitymentioning
confidence: 91%
“…On the other hand, several series of N-arylacetamide derivatives such as compounds C-D demonstrated high inhibitory activity against urease (Fig. 1) [23,24]. Based on these above-mentioned points, herein, we connected cysteine to N-phenylacetamide derivatives (compounds 5a-i) and N-(2-pyridyl)acetamide derivatives (compounds 5j-l) to achieve new urease inhibitors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the N-(2-pyridyl)acetamide series (compounds 5j-l), the 5-substituted compounds 5j and 5l respectively with methyl and chloro substituents showed approximately the same inhibitory activity against urease while 6-methyl derivative 5k shows less inhibitory activity compared to compounds 5j and 5l. The comparison of anti-urease activities of the new cysteine-N-arylacetamide derivatives 5a-l with cysteine derivatives A-B and N-arylacetamide derivatives C-D demonstrated that our new compounds inhibit the target enzyme urease much more potently than the template compounds A-D [17,23,24]. For example, as can be seen in Scheme 2, the comparison of IC 50 values of the new cysteine-N-arylacetamide derivatives 5 with their corresponding analogs of 2-((5-amino-1,3,4-thiadiazol-2-yl)thio)-N-arylacetamide derivatives D revealed that replacement of 2-((5-amino-1,3,4-thiadiazol-2-yl)thio) moiety of these compounds with cysteine unit improved anti-urease activity [24].…”
Section: In Vitro Urease Inhibitory Activitymentioning
confidence: 91%
“…On the other hand, several series of N-arylacetamide derivatives such as compounds C-D demonstrated high inhibitory activity against urease (Fig. 1) [23,24]. Based on these above-mentioned points, herein, we connected cysteine to N-phenylacetamide derivatives (compounds 5a-i) and N-(2-pyridyl)acetamide derivatives (compounds 5j-l) to achieve new urease inhibitors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Urease activity is also found in invertebrates like Aplysia californica (Carey et al, 2016) and Land snail Otala lactea (Liu et al, 2021a). Ammonia produced due to urease activity acts as proton acceptor enhanced the biological deposition of the Calcium carbonate (Liu et al, 2021b). Many Fungal species like Coccidioides immitis (Javadi et al, 2018), Rhodotorula spp.…”
Section: Sources Of Ureasementioning
confidence: 99%